2018
DOI: 10.1371/journal.pone.0190424
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of benzoxazinoids in wild emmer wheat, Triticum dicoccoides, at "Evolution Canyon", Mount Carmel, Israel

Abstract: Background"Evolution Canyon" (ECI) at Lower Nahal Oren, Mount Carmel, Israel, is an optimal natural microscale model for unraveling evolution-in-action, highlighting the evolutionary processes of biodiversity evolution, adaptation, and incipient sympatric speciation. A major model organism in ECI is the tetraploid wild emmer wheat, Triticum dicoccoides (TD), the progenitor of cultivated emmer and durum wheat. TD displays dramatic interslope adaptive evolutionary divergence on the tropical, savannoid-hot and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…avenae aphid, and it also highly accumulated HDMBOA-Glc (Figs 1 and 3B). Although DIMBOA levels were only slightly over-accumulated, it constitutes the predominant benzoxazinoid in wheat seedlings (Fig 4)[63]. The constitutive and herbivore-induced, specifically by cereal aphids, benzoxazinoid levels should be further explored to discover the corresponding genes involved in this pathway, mainly the unknown Bx6 , Bx7 and Bx10-Bx14 genes.…”
Section: Discussionmentioning
confidence: 99%
“…avenae aphid, and it also highly accumulated HDMBOA-Glc (Figs 1 and 3B). Although DIMBOA levels were only slightly over-accumulated, it constitutes the predominant benzoxazinoid in wheat seedlings (Fig 4)[63]. The constitutive and herbivore-induced, specifically by cereal aphids, benzoxazinoid levels should be further explored to discover the corresponding genes involved in this pathway, mainly the unknown Bx6 , Bx7 and Bx10-Bx14 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on different aspects BX biosynthesis over the past 50 years have reported that this class of metabolites is present in roots, root exudates, or root extracts of such species as maize [ 6 , 21 , 22 , 23 ], common wheat [ 24 , 25 , 26 , 27 ], emmer wheat [ 28 ], and rye [ 2 , 14 , 15 , 16 , 24 , 29 ]. Additionally, transcripts of Bx1 , the first gene controlling the BX biosynthesis pathway, have been detected in roots of rye [ 10 , 14 , 15 , 16 ], wheat [ 17 ], and maize [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 5, 2021. ; https://doi.org/10.1101/2021.03.05.434075 doi: bioRxiv preprint 1 1 wheat (Ben-Abu et al, 2018), and rye (Pérez and Ormenoñuñez 1991, Zasada et al, 2007, Schulz et al, 2013, Rakoczy-Trojanowska et al, 2018aRakoczy-Trojanowska et al, 2020). Also, transcripts of Bx1, the first gene controlling the BX biosynthesis pathway, have been detected in roots of rye (Tanwir et al, 2017, Rakoczy-Trojanowska et al, 2018a, b, 2020, wheat (Nomura et.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on different aspects BX biosynthesis over the past 50 years have reported that this class of metabolites is present in roots, root exudates, or root extracts of such species as maize (Neal et al, 2012, Neal and Ton 2013, Handrick et al, 2016; Cotton et al, 2019), common wheat (Pérez and Ormenoñuñez 1991, Belz and Hurle 2005, Stochmal et al, 2006, Villagrasa et al, 2006), emmer wheat (Ben-Abu et al, 2018), and rye (Pérez and Ormenoñuñez 1991, Zasada et al, 2007, Schulz et al, 2013, Rakoczy-Trojanowska et al, 2018a, b; Rakoczy-Trojanowska et al, 2020). Also, transcripts of Bx1 , the first gene controlling the BX biosynthesis pathway, have been detected in roots of rye (Tanwir et al, 2017, Rakoczy-Trojanowska et al, 2018a, b, 2020), wheat (Nomura et.…”
Section: Discussionmentioning
confidence: 99%